Analysis of the innovation and investment state in the sphere of industrial production of the Russian Federation - V. V. Degtyareva (Вестник университета)
The article presents an analysis of the innovative and investment state in the industrial production in the Russian Federation. The indicators “production and sales” of the Russian Federation, USA, Germany and Brazil are compared. An analysis of the Global Innovation Index and its components, in the context of seven indicators in the countries under study, is presented. Russia’s place in the IMD World digital competitiveness rating, is analysed. The main methods used in the study are analysis and generalisation, and the construction of chain indices based on statistical information on industrial indicators, the Global Innovation Index and the level of assessment of the digital competitiveness of four countries. Conclusions are drawn about the impact of the studied indicators on the economy and, at the moment, the Russia’s position is not entirely positive according to these indicators. It is proposed, to include these indicators in the methodology for managing corporate innovations and investments in industry under digitalisation to improve the economic level of the country as a whole.